Caribbean Renewal : Tackling Fiscal and Debt Challenges - Yartey, Charles Amo (International Monetary Fund, 2014)
Caribbean economies face high and rising debt-to-GDP ratios that jeopardize prospects for medium-term debt sustainability and growth. This book provides a comprehensive analysis of the challenges of fiscal consolidation and debt reduction in the Caribbean. It examines the problem of high debt in the region and discusses policy options for improving debt sustainability, including fiscal consolidation, robust growth, and structural reforms. The book also examines empirically the factors underlying global large debt reduction episodes to draw important policy lessons for the Caribbean. It also reviews the literature on successful fiscal consolidation experiences and provides an overview of past and current consolidation efforts in the Caribbean. The book concludes that the region needs a broad and sustained package of reforms to reduce debt ratios to more manageable levels and strengthen economic resilience.